Tinnitus and hyperacusis : facts, theories, and clinical implications - Eggermont, Jos J. (Elsevier Academic Press, 2022)
"Tinnitus and Hyperacusis: Facts, Theories, and Clinical Implications provides an overview on this burgeoning field, covering the underlying mechanisms and potential treatments for these disorders. The book begins with an overview of the etiology and genetics behind tinnitus and hyperacusis. The author then proposes two parallel neural pathways underlying these conditions and provides a basis for connecting animal to human research. Neurotransmitters, neuromodulators and immediate early genes are discussed, along with a detailed comparison of about a dozen models aimed at explaining tinnitus and hyperacusis, including the neurophysiological model, the neural synchrony model and the cortical map reorganization and filling-in model. Potential treatments of tinnitus and hyperacusis, from behavioral to non-invasive neuromodulation are also discussed. This book is written for clinical neuroscientists, audiologists, neuro-otologists, neurologists and clinical psychologists."--Publisher.